A Multi‐synergistic Platform for Sequential Irradiation‐Activated High‐Performance Apoptotic Cancer Therapy. (22nd October 2013) - Chen, Zhaowei; Li, Zhenhua; Wang, Jiasi; Ju, Enguo; Zhou, Li; Ren, Jinsong; Qu, Xiaogang
<x xml:space="preserve">Abstract</x> Artificial hyperthermia is an emerging technique to induce apoptotic cancer cell death. However, achieving effective hyperthermic apoptosis is often difficult, as cells typically acquire resistance to thermal stress. With the aid of sequential irradiation, highly integrated nanoassemblies based on reduced graphene oxide–ZnO nanoparticles–hyaluronic acid (rGo‐ZnO‐HA) can serve as a multi‐synergistic platform for targeted high‐performance apoptotic cancer therapy. The surface engineering of ZnO/graphene hybrid with multifunctional HA biomacromolecules simultaneously confers the system colloidal stability, biocompatibility, and a cancer cell targeting ability. After receptor‐mediated endocytosis, enzyme‐mediated fluorescence activation helps track cellular uptake and provides truly molecular imaging. Furthermore, the reactive oxygen species (ROS) generated by ZnO/rGo under light illumination can effectively sensitize cancer cells to the subsequent NIR laser‐induced apoptotic hyperthermia. In particular, photo modulation of cellular ROS to sensitize cells provides a novel approach to increase the efficacy of hyperthermic apoptosis. These findings suggest that a powerful apoptotic therapeutic platform could be achieved based on the multi‐synergistic platform.